Product Differentiation Strategies in Indonesian Green MSMEs: An Integrated Marketing Mix Analysis - Andriani, Nukeu Novia; Hurriyati, Ratih; Dirgantari, Puspo; Gaffar, Vanessa (Yayasan Sinergi Kawula Muda, 2026)
This study investigates product differentiation strategies employed by Indonesian green Micro, Small, and Medium Enterprises (MSMEs) through qualitative descriptive methodology. Semi-structured interviews were conducted with founder-owners of five green MSMEs in fashion and handicraft sectors across Java, analyzed using thematic coding (Braun & Clarke, 2006), SWOT-IFE/EFE evaluation, and QSPM prioritization. Findings revealed that effective differentiation requires holistic integration across Marketing Mix elements, characterized by three core dimensions: universal natural and upcycled material sourcing (100% adoption), premium pricing with 2 to 5 times markups, and export-oriented positioning with 70 to 90 percent international revenue. Strategic analysis positioned enterprises in the